2016
DOI: 10.1080/17441692.2016.1143524
|View full text |Cite
|
Sign up to set email alerts
|

HIV vulnerability and the erasure of sexual and gender diversity in Abidjan, Côte d'Ivoire

Abstract: In the fight against concentrated HIV epidemics, men who have sex with men (MSM) are often framed as a homogeneous population, with little attention paid to sexual and gender diversity and its impact on HIV vulnerability. This article draws on ethnographic research conducted in Abidjan, Côte d'Ivoire among les branchés – a local term encompassing several categories of same-sex desire and practice. In the context of increased HIV prevention programming targeting Ivoirian sexual and gender minorities, such diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Yet, the reappropriation of the term ‘MSM’ as an identity category has been noted, signalling the transformation of ‘MSM’ from epidemiological term to subject position [39]. In this study, numerous participants used the term’ MSM’ as an identity label, parallel to local parlance as has been noted in other settings among same-sex attracted men [40]. Neither continued reliance on the binary MSM/TW categories alone, nor the wholesale integration of local terminology in HIV programing would be sufficient; as argued by Thomann [40], the key to more responsive HIV programing is the recognition of the diverse lived experiences contained within local identities and how this intersects with other local and social realities to shape vulnerability to HIV.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Yet, the reappropriation of the term ‘MSM’ as an identity category has been noted, signalling the transformation of ‘MSM’ from epidemiological term to subject position [39]. In this study, numerous participants used the term’ MSM’ as an identity label, parallel to local parlance as has been noted in other settings among same-sex attracted men [40]. Neither continued reliance on the binary MSM/TW categories alone, nor the wholesale integration of local terminology in HIV programing would be sufficient; as argued by Thomann [40], the key to more responsive HIV programing is the recognition of the diverse lived experiences contained within local identities and how this intersects with other local and social realities to shape vulnerability to HIV.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, numerous participants used the term’ MSM’ as an identity label, parallel to local parlance as has been noted in other settings among same-sex attracted men [40]. Neither continued reliance on the binary MSM/TW categories alone, nor the wholesale integration of local terminology in HIV programing would be sufficient; as argued by Thomann [40], the key to more responsive HIV programing is the recognition of the diverse lived experiences contained within local identities and how this intersects with other local and social realities to shape vulnerability to HIV. Indeed, the differing experiences and perspectives among the various sexual and gender identities, even within the same identity group, documented in this study highlights the importance of service provision that can appropriately cater for different groups and their heterogenous needs.…”
Section: Discussionmentioning
confidence: 99%
“…In places such as Côte d'Ivoire, for example, fear impeded the radio journalists who had become allies to the project from easily recruiting people as guests to their programs. Structural interventions that fail to take this context into account run a high risk of undermining rather than furthering the goal of dismantling stigma and discrimination and may endanger local communities [59,60,63,64,[67][68][69]. A major tenet of the approach to this project was deference to local understanding of what adaptations and approaches were best and how to implement those in ways that were safe.…”
Section: Discussionmentioning
confidence: 99%
“…Even though not all persons in the film are transvestites, here the definition of the woubi is clearly on the feminine side of the spectrum, albeit in a more or less visible way. Subsequent research has confirmed the persistence of these categories through the following decades (Nguyen 2005;Thomann 2016;Thomann and Corey-Boulet 2017), although there have been notable shifts, particularly in connection with the development of the internet (Broqua 2013b).…”
Section: Differentiated Gender Roles Between Biologically Male Sex Pa...mentioning
confidence: 95%